Dibutyl phthalate modulates phenotype of granulocytes in human blood in response to inflammatory stimuli. (15th October 2018) - Maestre-Batlle, Danay; Pena, Olga M.; Huff, Ryan D.; Randhawa, Abnashi; Carlsten, Christopher; Bølling, Anette K.
Highlights: DBP is a plasticizer linked to airway diseases with limited experimental data describing immune-modulating effects. DBP reduced TNFα and IFNγ release and altered granulocytes marker expression in response to immune stimuli in vitro . Whole blood assay is a valuable model to study effects of environmental contaminants on inflammation and cellular function. Current results regarding immune-modulating effects of DBP merit further in vitro and in vivo investigations. Abstract: Background: Phthalates are plasticizers used in many common commercial products. They are ubiquitous environmental contaminants and epidemiological studies suggest that phthalate exposure is associated with development or worsening of airway diseases. Dibutyl phthalate (DBP) is a type of phthalate, found in high concentrations in indoor air, which appears to have a high inflammatory potential. In vitro studies on innate immune cells like macrophages have shown a reduction in phagocytic and antigen-presenting capacity and decreased production of stimuli-induced cytokines after DBP exposure. Objective: We aimed to assess how DBP may alter the in vitro cellular and humoral innate immune response to inflammatory stimuli in blood innate immune cells. Methods: Human whole blood was stimulated with inflammatory stimuli (lipopolysaccharide (LPS), resiquimod (R848) and phorbol 12-myristate 13-acetate (PMA)) in the presence or absence of DBP. The expression of surface markers CD16, CD24, CD69 and CD14 on granulocytes and monocytes was quantified by flow cytometry analysis. The release of TNFα, IFNγ, IL8 and IL10 cytokines was measured by ELISA. Results: The presence of DBP reduced the inflammatory stimuli-induced expression of CD24 on neutrophils and eosinophils and CD69 on activated eosinophils, whereas expression of CD16 on neutrophils was increased. DBP also had a dampening effect on the release of pro-inflammatory mediators TNFα and IFNγ in response to the inflammatory stimuli. Conclusions: These responses may reflect an immunosuppressive effect of DBP through impairment of immune cell function.